Klenteng Mosque’s Religious Moderation: Intercultural Communication and Remarking Da’wah of Wasathiyah Islam - Mukti Ali; Ulfiayatun Nadhifah; Wuri Arenggoasih (Jurnal Dakwah Risalah, 2022)
This study aims to determine the understanding of religious moderation related to the existence of the Hidayatullah Temple mosque as a form of acculturation of faith in Salatiga. The role of the manager of the Hidayatullah Temple Salatiga is spreading the value of the Islamic concept of wasathiyah, and determining the supporting and inhibiting factors of management. This type of research is qualitative research by conducting field research. The results of the study indicate that the existence of the Hidayatullah Temple Mosque is clear evidence of religious tolerance in intercultural communication and a manifestation of religious understanding regarding religious moderation in Salatiga. The architectural style of the Hidayatullah Temple is an instrument of acculturation of faith and religious harmony in Salatiga which has two essential roles, namely the formal and informal roles in spreading Islamic moderation values. The strategic location of the mosque makes it easy to coordinate and collaborate with various parties as a supporting factor in improving intercultural communication.